Strikingly Bacteria-Like and Gene-Rich Mitochondrial Genomes throughout Jakobid Protists - Burger, Gertraud (Oxford University Press, 2013)
The most bacteria-like mitochondrial genome known is that of the jakobid flagellate Reclinomonas americana NZ. This genome also encodes the largest known gene set among mitochondrial DNAs (mtDNAs), including the RNA subunit of RNase P (transfer RNA processing), a reduced form of transfer–messenger RNA (translational control), and a four-subunit bacteria-like RNA polymerase, which in other eukaryotes is substituted by a nucleus-encoded, single-subunit, phage-like enzyme. Further, protein-coding genes are preceded by potential Shine–Dalgarno translation initiation motifs. Whether similarly ancestral mitochondrial characters also exist in relatives of R. americana NZ is unknown. Here, we report a comparative analysis of nine mtDNAs from five distant jakobid genera: Andalucia, Histiona, Jakoba, Reclinomonas, and Seculamonas. We find that Andalucia godoyi has an even larger mtDNA gene complement than R. americana NZ. The extra genes are rpl35 (a large subunit mitoribosomal protein) and cox15 (involved in cytochrome oxidase assembly), which are nucleus encoded throughout other eukaryotes. Andalucia cox15 is strikingly similar to its homolog in the free-living α-proteobacterium Tistrella mobilis. Similarly, a long, highly conserved gene cluster in jakobid mtDNAs, which is a clear vestige of prokaryotic operons, displays a gene order more closely resembling that in free-living α-proteobacteria than in Rickettsiales species. Although jakobid mtDNAs, overall, are characterized by bacteria-like features, they also display a few remarkably divergent characters, such as 3′-tRNA editing in Seculamonas ecuadoriensis and genome linearization in Jakoba libera. Phylogenetic analysis with mtDNA-encoded proteins strongly supports monophyly of jakobids with Andalucia as the deepest divergence. However, it remains unclear which α-proteobacterial group is the closest mitochondrial relative.